A design of tuned mass damper with piezoelectric stack energy harvester and two-stage force amplification frame - Ngoc, Nguyen Anh; Nang, Tong Duc; Tuan, Vu Anh; Anh, Nguyen Dong; Viet, La Duc; Anh, Tran Tuan; Linh, Nguyen Ngoc (Vietnam Journal of Mechanics, 2024)
The paper deals with a novel tuned mass damper (TMD) with an energy harvester consisting of a combination of piezo stacks and two-stage force amplification frames connected in series with TMD springs (TMD-2sPSFAFs). The governing equations of 2sPSFAF are established first, followed by those of TMD-2sPSFAF. It will be demonstrated that the reduced order model of the series combination of 2sPSFAF and TMD spring is an equivalent piezo stack energy harvester. Using the optimal results according to the fixed point theory, the conditions for selecting stiffnesses of piezo stacks and TMD spring are obtained. Next, a numerical examination of the electromechanical system reveals that the voltage amplitude curve has a fixed point independent of TMD spring stiffness. Furthermore, an effective stiffness of the TMD spring would be found to ensure that the peaks of mechanical magnification and voltage amplitude curves are of equal heights.